A rare form of cardiomyopathy: left ventricular non-compaction cardiomyopathy - Aditya Goud; Sriram Padmanabhan (Greater Baltimore Medical Center, 2016)
Left ventricular non-compaction is a recently recognized, rare form of cardiomyopathy. It is based on the arrest of endomyocardial morphogenesis during embryogenesis. It was first described in 1984 by Engberding who described it as isolated 'sinusoids' within the LV. Right now its prevalence is estimated at 0.014 to 1.3 and 3-4% in heart failure patients. Its clinical manifestations are highly variable, ranging from no symptoms to disabling congestive heart failure, arrhythmias, and systemic thromboemboli. Doppler Echocardiogram is considered the diagnostic procedure of choice and treatment is symptomatic management of its symptoms and complications.